Actinomadura violacea sp. nov., a madurastatin A1-producing strain isolated from lichen in Thailand. Issue 12 (6th December 2021) - Kanchanasin, Pawina; Phongsopitanun, Wongsakorn; Yuki, Masahiro; Kudo, Takuji; Ohkuma, Moriya; Nakashima, Takuji; Tanasupawat, Somboon
Abstract : An actinomycete strain, LCR2-06 T, isolated from a lichen sample on rock collected from Chiang Rai Province (Pong Phra Bat Waterfall), Thailand, was characterized using a polyphasic approach. The strain grew at 25–45 °C, pH 6–11 and on International Streptomyces Project 2 agar plate with 5 % (w/v) NaCl. It contained meso -diaminopimelic acid as the diamino acid in whole-cell hydrolysates. Rhamnose, ribose, xylose, madurose, glucose and galactose were detected as whole-cell sugar hydrolysates. Mycolic acids were absent. The N -acyl type of muramic acid was acetyl. The strain contained C16 : 0, TBSA 10-methyl C18 : 0 and 2-hydroxy C16 : 0 as the predominant fatty acids and MK-9(H6 ), MK-9(H4 ) and MK-9(H8 ) as the major menaquinones. The major polar lipids were diphosphatidylglycerol, phosphatidylinositol and unidentified phospholipid. The draft genome of strain LCR2-06 T was closely related to Actinomadura barringtoniae TBRC 7225 T (99.2 %), Actinomadura nitritigenes NBRC 15918 T (98.8 %), Actinomadura montaniterrae TISTR 2400 T (98.5 %) and Actinomadura physcomitrii JCM 33455 T (97.9 %). The draft genome of LCR2-06 T was 11.1 Mb with 10 588 coding sequences with an average G+C content of 72.7 mol%. Results of genomic analysis revealed that the ANIb and ANIm values between strain LCR2-06 T and A. montaniterrae TISTR 2400 T were 90.0 and 92.0 %, respectively. The digital DNA–DNA hybridization value was 43.9 % in comparison with the draft genome of A. montaniterrae TISTR 2400 T . The strain produced an antibacterial compound active against Bacillus subtilis ATCC 6633 and Kocuria rhizophila ATCC 9341. The results of taxonomic analysis suggested that strain LCR2-06 T represented a novel species of the genus Actinomadura for which the name Actinomadura violacea sp. nov. is proposed. The type strain is LCR2-06 T (=JCM 33065 T =KCTC 49547 T =NBRC 114810 T =LMG 32136 T =TISTR 2935 T ).